Compensation and Benefits as a Tool to Improve the Performance of MSME Employees in Gabru Village, Gurah District - Kristanti, Desi; Yunanto, Yogi; Komari, Ana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to evaluate the impact of compensation and benefits on employee efficiency in Micro, Small and Medium Enterprises (MSMEs) in Gabru Village, Gurah District. The focus is not only on financial incentives, but also employee motivation and company productivity. Challenges in designing compensation systems in MSMEs include limited resources, simple organizational structures, and dynamic markets. Factors such as the uncertainty of the business environment and organizational culture influence its effectiveness. Empirical studies show that fair compensation can increase employee satisfaction and performance. By considering the unique factors of MSMEs, business owners can develop effective strategies. This research uses a qualitative approach involving interviews, surveys, literature reviews, and secondary data analysis. Findings show that compensation and benefits programs have a positive impact on retaining quality employees and improving organizational performance.